Effectiveness of joint mobilization in elderly patients with chronic cervical pain: a systematic review (Research, Society and Development, 2021)
Objectives: To identify the effectiveness of joint mobilization in elderly patients with chronic neck pain. Methods: The study was based on a systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), conducted in the following electronic databases: PEDro (Physiotherapy Evidence Database), PubMed (National Library of Medicine, USA, USA) and Central (the Cochrane Libary Collaboration ECA Database). The research was carried out using the descriptors: “Manual therapy”. “Cervical pain”, “Chronic pain”, “Elderly” among the keywords with the purpose of optimizing the results and their descriptors in English: “Manual therapy”, “Neck pain”, “Chronic pain”, “Aged” and the crossing of the words through the Boolean operators “AND” and “OR”. Results: The results showed that the joint mobilization technique was effective in improving chronic neck pain. Conclusion: The technique of joint mobilization in elderly patients with cervical pain, proves the decrease in pain and increase in functional capacity, providing a better quality of life and showing effectiveness in the short and long term by improving the clinical picture of cervical pain.